2021
DOI: 10.3390/antibiotics10030340
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Risk Factors in Prosthetic Joint Infections by multidrug-resistant Gram-negative Bacteria: A Retrospective Cohort Study

Abstract: Gram-negative bacteria (GNB), including multidrug-resistant (MDR) pathogens, are gaining importance in the aetiology of prosthetic joint infection (PJI). This retrospective observational study identified independent risk factors (RFs) associated with MDR-GNB PJI and their influence on treatment outcomes. We assessed MDR bacteria causing hip and knee PJIs diagnosed at a Brazilian tertiary hospital from January 2014 to July 2018. RFs associated with MDR-GNB PJI were estimated by bivariate and multivariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Unfortunately, these results do not represent what is has been achieved in other countries. In Switzerland, the proportion of prescriptions filled with generic drugs is only about 17 % to 23 %, while in France it is about 30 % to 40 % -far from Germany and Great Britain, with 80 % to 82 % and 83 % to 85 %, respectively (Wouters et al, 2017;Decollogny et al, 2011; Organisation for Economic Co-Operation and Development (OECD), 2019). Nevertheless, without the generic molecules of daptomycin and linezolid, the costs associated with ETs during the study period could not have been stable and would have increased dramatically, especially in 2019 with the use of tedizolid, ceftolozane-tazobactam, and ceftazidime-avibactam.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, these results do not represent what is has been achieved in other countries. In Switzerland, the proportion of prescriptions filled with generic drugs is only about 17 % to 23 %, while in France it is about 30 % to 40 % -far from Germany and Great Britain, with 80 % to 82 % and 83 % to 85 %, respectively (Wouters et al, 2017;Decollogny et al, 2011; Organisation for Economic Co-Operation and Development (OECD), 2019). Nevertheless, without the generic molecules of daptomycin and linezolid, the costs associated with ETs during the study period could not have been stable and would have increased dramatically, especially in 2019 with the use of tedizolid, ceftolozane-tazobactam, and ceftazidime-avibactam.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) affects over 30% of the general population over the age of 30 and over 65% over the age of 65 [1,2]. Joint arthroplasty is an expensive procedure, depending on the area of operation, age and weight of the patient, the extent of the procedure, type of prosthesis and components used, however in most cases it is the only way to effectively and completely cure disability in millions of people around the world [3][4][5]. Despite the dynamic development in the field of materials engineering, it was not possible to develop an artificial friction node that would be universal and sufficiently failure-free to be implanted in all patients.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, we also found that E. coli was signi cantly more frequently cultured in Group 2 than in Group 1. The prevalence of E. coli PJI is approximately 8% [24], and this resistant strain is highly related to poor outcomes in two-stage revision arthroplasty [25]. However, for DM patients with E. coli PJI, our study is the rst to identify the relative risk.…”
Section: Discussionmentioning
confidence: 95%